LncRNA Bigheart stimulates Regulator of calcineurin 1 (Rcan1) expression in an auto-amplification loop that stimulates calcineurin-NFAT signalling in heart failure. (14th October 2021) - Mangraviti, N; Ruhle, F; Martens, L; Kinet, V; Hegenbarth, J C; Seyer, S; Olieslagers, S; Stoll, M; De Windt, L J
Abstract: Background: Cardiac hypertrophy precedes many heart diseases and understanding its molecular basis remains one of the greatest challenges in cardiovascular medicine. Recent studies highlighted the sporadic involvement of long noncoding RNAs (lncRNAs) in cardiac development and disease but our understanding of lncRNAs in heart failure is still limited. Results: Expression profiling of lncRNAs in failing mouse hearts revealed dysregulation of "Bigheart", a novel lncRNA that is evolutionary conserved. Bigheart overexpressed using a serotype 9 adeno-associated virus (AAV) in neonatal rat cardiomyocytes (NRCMs) induced spontaneous hypertrophy, while silencing this lncRNA with specific siRNAs blunted the hypertrophic response in agonist-stimulated cardiomyocytes. GapmeR-mediated silencing of Bigheart prevented transverse aortic constriction (TAC)-induced pathological cardiac remodeling in the mouse in vivo. Mechanistically, analysis of the Bigheart genomic locus revealed several binding sites for the transcription factor nuclear factor of activated T-cells (NFAT), a downstream transcription factor of the pro-hypertrophic calcineurin-NFAT signaling cascade. The sensitivity of Bigheart transcriptional induction for calcineurin-NFAT signalling was further demonstrated by luciferase assays using a Bigheart promoter-luciferase construct. Finally, RNA-sequencing of Gapmer-silenced mouse hearts and chromatin isolation by RNA purification (ChIRP) coupled to mass spectrometry (MS), revealed that Bigheart interacts with heterogeneous nuclear ribonucleoproteins (hnRNPs) and High Mobility Group Box 1 (HMGB1) acts in trans to stimulate the transcription of Regulator of calcineurin 1 (Rcan1), a facilitator of calcineurin-NFAT signaling. Conclusions: These results indicate that lncRNA Bigheart constitutes a positive feedforward loop in hypertrophic signaling and a promising target to attenuate maladaptive cardiac hypertrophy FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Maastricht university